Modified sweep algorithm with fuzzy-based parameters for public bus route selection - 465973 Gunadi Widi Nurcahyo (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2003